Accounting Towards Islamic Spirituality in The Perspective of Philosophy of Science - La Angga; Nitri Mirosea; Nur Asni (Eduvest - Journal of Universal Studies, 2025)
The development of studies in a scientific field is often not accompanied by equal progress in ethical and moral aspects, which causes the practice of theory to not integrate with spiritual values. This condition causes the implementation of human intellectual disharmony with the expected morality in society. As a foothold in the development of science, philosophy of science must be used as a basis for reformulating the moral content and spiritual values of modern science in order to redefine the foundations of science and technology, both at the levels of epistemology, ontology and axiology. Accounting as part of the object of study of science and knowledge must be directed at reformulating spiritual values that alienate ethics and morals. Modern accounting science which precipitates free material and values makes accounting towards materialistic, egoistic, secularistic and atheistic. Coupled with the assumption that humans are homo economicus, who are opportunistic, greedy and risk themselves, increasingly color the cases that occur. Restructuring the accounting conceptual framework that leads to Islamic spiritual values based on truth and justice is very important to do. Because, in the context of modern accounting science which precipitates material and is free of value it will bring accounting science to capitalist thinking.